SHARING TAKJIL, BREAKING THE BREAK TOGETHER AND SUPPORTING THE SERDANG BEDAGAI STUDENTS ASSOCIATION ORPHANAGE WITH RADJA PUBLIKA AND RADJA PUSTAKA LHOKSEUMAWE NORTH ACEH 2024 - Rico Nur Ilham; Irada Sinta; Muammar Khaddafi; Likdanawati; Hamdiah; Sutriani (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Sharing takjil, breaking the fast together, and providing donations to children from orphanages are social initiatives that aim to strengthen relationships between individuals and provide assistance to those in need, especially children from orphanages, realizing the concern of lecturers and administrators of Radja Publica Grub andIKMA SERGAI in increasing the sense of social concern for others, instilling human values ​​so that the next generation has a strong sense of empathy. This is basedLaw Number 4 of 1979, LN.19979-32 concerning child welfare, article 4 (1) states that "children who do not have parents have the right to receive care from the state or person or body".These activities include distributing takjil to people who are fasting, breaking the fast together to increase the sense of togetherness, and providing compensation to children in orphanages as a form of social care.